Teacher update course in palliative care: the use of active methodologies (Research, Society and Development, 2022)
The purpose of this article is to present the process of elaboration and the methodological resources of a teaching update course in palliative care. As most faculty of medical schools graduated prior to the 2014 national curriculum guidelines, training was predominantly technical, aimed at healing over care. The objective of the course is to train teachers on knowledge and skills on the subject of palliative care, on the importance of dealing with finitude, death and bereavement; and develop basics of palliative care, communication and grief. To this end, the didactic sequence was used: pre-classroom activity (text for prior reading and recorded class with technical communication skills); first face-to-face meeting (reception of participants; questionnaire on communication; discussion of perceptions about the text; exhibition of film excerpts with communication scenes; discussion of the feelings mobilized; role-play followed by feedback and; feedback from the first meeting); second face-to-face meeting: reading and processing the problem situation – “But isn’t palliative care letting it die?” followed by feedback from the second meeting; third face-to-face meeting with processing of the new synthesis, followed by feedback from the third meeting and; general course feedback. The systematization of the teacher update course in palliative care can favor the reproducibility of this educational product, contributing to improve the quality of teacher and student training in the health area. The use of active methodologies in the construction of the course makes it more attractive and facilitates the process of acquiring knowledge and student protagonism.